Gangguan Makan pada Remaja Dipengaruhi Oleh Media Sosial Melalui Citra Tubuh Negatif - Tezsa Leonyka Esther Tunga (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction; Adolescence is one phase in life that undergoes a transitional period accompanied by changes in physical, cognitive, and socio-emotional aspects. Eating disorders are one of the phenomena in the focus of public health that are rife in adolescence. Aim; to determine the effect of social media on eating disorders through body image. Method; The literature review method with the PRISMA approach using 11 relevant articles. Results: The study results found the main findings that social media could affect eating disorders through negative body image in adolescents, both boys, and girls. The negative body image possessed by teenagers can occur due to the use of social media that is not adequately limited, both in terms of intensity and content accessed by displaying a body shape that is considered ideal and attached to the impression of being thin and shaped. Conclusions; The influence is given by social media through negative body image on eating disorders can be recommended for intervention in the form of increasing literacy in the use of social media so that it does not harm the mindset and attitudes of adolescents.